Analysis of the Influence of Macroeconomic Indicators on Unemployment Rate: Evidence in ASEAN - Muhammad, Rezta Kurniardi; Arif, Muhammad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to analyze the influence of economic growth, foreign direct investment, corruption perception index, consumer price index, and human development index on unemployment in ASEAN from 2018 to 2022. This research is quantitative in nature, utilizing panel data analysis. The population in this study consists of the 11 ASEAN member countries with annual data from 2018 to 2022. Data were obtained by accessing the websites of the World Bank, Transparency International, UNDP, and Trading Economics. Subsequently, the data were processed using Eviews 12 software. The results of the study employing the Fixed Effects Model (FEM) demonstrate that unemployment is negatively influenced by economic growth, consumer price index, and human development index, whereas it is positively affected by the corruption perception index. Conversely, foreign direct investment does not exert a noteworthy impact on unemployment within the ASEAN region. Research on unemployment in ASEAN countries has been inconsistent; further investigation is needed to address this gap. Factors contributing to unemployment, particularly within this region's context, require deeper understanding. Additionally, this research also encompasses a new dimension: the impact of corruption, which has been underexplored previously.